Leaf spot of Ligustrum japonicum caused by Diaporthe eres newly reported in China. (February 2023) - Liao, Yang-Chun-Zi; Wan, Yu; Si, Yuan-Zhi; Geng, Ji-Xin; Li, De-Wei; Zhu, Li-Hua
Abstract: Ligustrum japonicum is widely cultivated as ornamental and hedges in residential areas, parks and roadsides in China. A leaf spot disease has been extensively observed on L. japonicum in Nanjing, Jiangsu, China since September 2020. This disease not only affects the plant's growth, but also leads to unsightly appearances. A fungal species was isolated from symptomatic leaves. Its colony on PDA was white with aerial mycelia; the reverse of the colony was white. Both α- and β-conidia were observed. Morphological features of this fungus matched those of Diaporthe spp. For accurate identification, partial sequences of the internal transcribed spacer region (ITS), elongation factor 1-alpha ( EF ), calmodulin ( CAL ), beta-tubulin ( TUB ), and histone H3 ( HIS ) genes were amplified and sequenced. Phylogenetic trees verified that this species is Diaporthe eres . Pathogenicity tests were conducted by inoculating healthy leaves with mycelium plugs and Koch's postulates were confirmed by pathogen re-isolation and identification. This is the first report that D. eres causes L. japonicum leaf spot in China. Highlights: A leaf spot disease was extensively observed on Ligustrum japonicum in China. Diaporthe eres was identified based on morphological as well as cultural characteristics, and phylogenetic analyses. We confirmed D. eres was the causal agent of leaf spot on L. japonicum.